2000
DOI: 10.1002/1526-4998(200010)56:10<882::aid-ps226>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Pheromone-based integrated pest management to control the diamondback mothPlutella xylostella in cabbage fields

Abstract: Biorational and regular insecticide applications were evaluated for management of the diamondback moth (DBM) Plutella xylostella in cabbage (Brassica oleracea var capitata) in Karnataka State, India, in 1996 and 1997. The IPM programme, based on the pheromone trap catch threshold of eight moths per trap per night, included utilization of the parasitoid Cotesia plutellae.(250 000 adults ha À1 ), the predator Chrysoperla carnea (2500 eggs ha À1 ), the neem-based chemical nimbecidine (625 ml ha À1 ), the bacteriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
2
34
0
2
Order By: Relevance
“…Neem extracts are reported to affect over six hundred species of pests (Sivasakthi et al, 2013). Reddy and Guerrero (2000) suggested that neem had the potential to be used as a good alternative to conventional insecticides in IPM programs. In the current study, neem effectively suppressed C. cinctus populations (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Neem extracts are reported to affect over six hundred species of pests (Sivasakthi et al, 2013). Reddy and Guerrero (2000) suggested that neem had the potential to be used as a good alternative to conventional insecticides in IPM programs. In the current study, neem effectively suppressed C. cinctus populations (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic sex pheromone has been utilized to monitor and control DBM (Môttus et al, 1997;Reddy and Guerrero, 2000a). In China, more farmers prefer mass trapping to mating disruption with sex pheromone lures for control of insect pests because it is convenient and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Sex pheromone-baited traps have been developed to monitor diamondback moth in canola (Chisholm et al 1983) and commercially available lures (ConTech Enterprises Inc., Delta, BC, Canada) are currently used in the government-funded Prairie Pest Monitoring Network (http:// nlwis-snite2.agr.gc.ca/ppmn/loginFormEn.jsp) to detect the arrival of migrant diamondback moths into the Prairie provinces. Pheromone-baited traps are used to predict population densities of diamondback moth larvae in cabbage (Walker et al 2003) and threshold trap catch is used to time control measures in cabbage (Reddy and Guerrero 2000). Applications such as these for sex pheromone-baited traps in canola would assist in the management of diamondback moth in this region.…”
mentioning
confidence: 99%